ANTISIPATIF PROBLEMATIKA PENDIDIKAN BERBASIS TEKNOHUMANISTIK DENGAN PENDIDIKAN SISTEM AMONG KI HAJAR DEWANTORO - I Made Ariasa Giri (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2018)
Effective collaboration in learning education will tercerim of application of EducationalModel of Technohumanistik based on the method of education system among Ki Hajar Dewantara.Educational method of teaching method based on the asad, asah and foster, it is seen in theEducational Technique Model which adheres to the learning education paradigm that givesmore role to the learner to develop the skill needed for him with the principle of educationimplementation needs to be based on “Ing ngarso sung tulodho, Ing madyo mangun karso, Tutwuri handayani “so that the resulting output has a strong character and identity that is able tothink globally without leaving the existing values and norms. With the application ofteknohumanistik education, students can keep abreast of global developments but still based onthe values & local genius aspects in meeting global challenges in the context of education, sothat human humanizing process can not be separated from the national character can be fulfilledto achieve a better future education.